PKM Communicative English Program (CEP) di Program Studi Pendidikan Bahasa Inggris Universitas Islam Riau Tahun Akademik 2018/2019 - Hadijah, Sitti; Shalawati, Shalawati (Community Education Engagement Journal, 2019)
Facilitating low performance students with extra curricular activities is highly required by them as an effort that can be done to enhance the students’ English skills. Meanwhile, the students’ extra curricular activities should be regularly applied. In this case, the writers finally decided to run a program, namely Communicative English Program (CEP), a communicative learning course which was designed to help the third year students of English Department in Universitas Islam Riau to improve their confidence in using English. Initally, CEP consists of several programs with different main purposes, but the current program is called as CEP I, conducted in English Department particularly to help the students in producing grammatically correct sentences that will simultaneously improve their self-confidence.